Exploration of C–H and N–H-bond functionalization towards 1-(1,2-diarylindol-3-yl)tetrahydroisoquinolines - Ghobrial, Michael; Mihovilovic, Marko D.; Schnürch, Michael (Beilstein Journal of Organic Chemistry, 2014)
The synthesis of 1,2,3-trisubstituted indoles was investigated. More specifically, straightforward synthetic routes towards 1-(1,2-diarylindol-3-yl)-N-PG-THIQs (PG = protecting group, THIQ = tetrahydroisoquinoline) employing transition metal-catalyzed C–H and N–H-bond functionalization were explored. It was found that the synthesis of the target compounds is strongly dependent on the order of events. Hence, depending on the requirements of a synthetic problem the most suitable and promising pathway can be chosen. Additionally, a new synthetic approach towards 1,2-diarylindoles starting from 1-arylindole could be established in the course of our investigation by using a palladium-catalyzed protocol. Such 1,2-diarylindoles were successfully reacted with N-Boc-THIQ to furnish 1,2,3-trisubstituted indoles as target compounds. Furthermore, regioselective N-arylation of protected and unprotected 1-(indol-3-yl)-THIQs was successfully conducted using either simple iron or copper salts as catalysts.
Keywords: Buchwald–Hartwig coupling; C–C coupling; C–H functionalization; iron catalysis; regioselective arylation